2018
DOI: 10.1038/s41467-018-05529-2
|View full text |Cite
|
Sign up to set email alerts
|

Local orthorhombic lattice distortions in the paramagnetic tetragonal phase of superconducting NaFe1−xNixAs

Abstract: Understanding the interplay between nematicity, magnetism and superconductivity is pivotal for elucidating the physics of iron-based superconductors. Here we use neutron scattering to probe magnetic and nematic orders throughout the phase diagram of NaFe1−xNixAs, finding that while both static antiferromagnetic and nematic orders compete with superconductivity, the onset temperatures for these two orders remain well separated approaching the putative quantum critical points. We uncover local orthorhombic disto… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 61 publications
1
21
0
Order By: Relevance
“…Theoretically, the electronic nematic phase and associated resistivity anisotropy is expected to only occur below the tetragonal-to-orthorhombic phase transition temperature T s [7]. Although recent neutron pair distribution function and Lamor diffraction experiments on dif-ferent classes of iron pnictides including Sr 1−x Na x Fe 2 As 2 [35] and NaFe 1−x Ni x As [36] reveal clear evidence for local orthorhombic lattice distortions in temperatures well above T s , these local lattice distortions are evenly distributed along the two orthorhombic lattice directions and therefore not expected to induce resistivity anisotropy. The clear presence of resistivity [12,13], spin excitation [19][20][21][22], and orbital population anisotropy [37] in the paramagnetic phase of iron pnictides can arise from the interaction of applied uniaxial pressure with nematic susceptibility and associated spin excitations through magnetoelastic coupling [38].…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, the electronic nematic phase and associated resistivity anisotropy is expected to only occur below the tetragonal-to-orthorhombic phase transition temperature T s [7]. Although recent neutron pair distribution function and Lamor diffraction experiments on dif-ferent classes of iron pnictides including Sr 1−x Na x Fe 2 As 2 [35] and NaFe 1−x Ni x As [36] reveal clear evidence for local orthorhombic lattice distortions in temperatures well above T s , these local lattice distortions are evenly distributed along the two orthorhombic lattice directions and therefore not expected to induce resistivity anisotropy. The clear presence of resistivity [12,13], spin excitation [19][20][21][22], and orbital population anisotropy [37] in the paramagnetic phase of iron pnictides can arise from the interaction of applied uniaxial pressure with nematic susceptibility and associated spin excitations through magnetoelastic coupling [38].…”
Section: Discussionmentioning
confidence: 99%
“…The increase in the strain broadening S 202 can have a similar origin [27] and does not indicate macroscopic symmetry lowering. Indeed, in systems with the symmetry lowering an anisotropic strain broadening will usually precede the symmetry-lowering phase transition and diverge upon approaching the transition from above [28]. This does not happen in Fe 2 Mo 3 O 8 , where the high-resolution synchrotron data collected both right above and well below T N reveal only a weak broadening of the h0l reflections [ Fig.…”
Section: (E)]mentioning
confidence: 99%
“…T result implies that the strong specific-heat peak in zero-field at is a novel combined structural, magnetic and superconduct first-order transition, in which a re-entrance of the C 2 -SD phase occurs. How exactly a magnetic field tunes the system fr 14 (symbols) for the thermal expansion distortion corrected for the effect of the applied force, d 0 , for the samp (see Supplementary Figs 1 and 2 for details on the measurement of th…”
Section: Random-field Ising-nematic Modelmentioning
confidence: 99%
“…In the iron-based superconductors, signatures of C 4 symmetry breaking and short-range nematic order have often been found well above the bulk nematic phase transition temperature [12][13][14][15], especially from local probe measurements using scanning tunneling microscopy (STM) [16] and nuclear magnetic resonance (NMR) [17][18][19][20][21][22][23][24]. More recently, x-ray and neutron pair distribution function (PDF) studies have revealed the locally orthorhombic nature of the tetragonal paramagnetic phase in the (Sr,Na)Fe 2 As 2 system [25].…”
Section: Introductionmentioning
confidence: 99%